Detection of DNA Changes in the Parp-1 Gene in the Small Intestine Tissue of Male White Rats Exposed to Pesticides Using PCR - Muhammad Diki Juliandi; Dewi Yudiana Shinta; Evana Kamarudin (Universitas Nahdlatul Ulama Surabaya, 2026)
Excessive exposure to pesticides can damage DNA. This paper analyzes the effects of pesticide exposure on the small intestine tissue (ileum) of white rats (Rattus Norvegicus), focusing on DNA mutation, particularly in the Parp-1 gene. This paper was an experimental study with a posttest-only design. It involved 18 male white rats (Rattus Norvegicus), divided into 5 groups: dose 1 (1.1 ml) and dose 2 (2.2 ml) groups for 7 days of oral pesticide administration, dose 1 (1.1 ml) and dose 2 (2.2 ml) groups for 14 days of oral pesticide administration, and a control group. Blood samples were collected to measure acetylcholinesterase enzyme levels, and ileal tissue was collected for analysis of PARP-1 gene expression. DNA was isolated from the ileum of the small intestine, and amplification was performed using forward (5'- TGGCCAAAAAGAAATCTAAG-3') and reverse (5'-ATCCCCAGTACAGTAA TAAG-3') primers. Results found that the lowest average acetylcholinesterase levels were observed in the high-dose group (2.2 ml) with a treatment period of 14 days, namely 18%. In contrast, the highest average acetylcholinesterase levels were observed in the low-dose group (1.1 ml) with a 7-day treatment period, namely 49%. Furthermore, the PARP-1 gene was detected by band thickness (band) in samples ranging from 260 to 347, using the PCR method with PARP-1 gene primers. Thus, pesticide exposure changes PARP-1 gene expression in the small intestinal tissue of white rats (Rattus Norvegicus). It indicates that pesticides can cause DNA mutation, leading to damage in the rat's small intestinal tissue.